Teoria e métodos ecológicos e evolutivos aplicados a dados humanos: de diversidade biocultural à propagação de doenças - Borges, Christielly Mendonça (2022)
Traditionally, Homo sapiens have been an exclusive subject of study of the humanities. The resistance of natural scientists to study humans from an eco-evolutionary point of view is easily explained by the unfolding of the 20th century eugenics movement. Starting from the scientific advances on the low genetic variability between human populations and the spatial patterns of language diversity, the idea of a non-biological human diversity emerged, where humans form numerous cultural groups with complex global spatial and demographic patterns. In this thesis, we apply eco-evolutionary theories and methods to human data, focusing on different aspects of linguistic diversity, following a macroecological approach and also analyzing the propagation dynamics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In Chapter 1, we reviewed how the evolution of languages and species goes far beyond mere analogies and has accumulated a growing literature that supports these parallels at both micro and macroevolutionary scales. In Chapter 2 we created a dialect quiz to collect linguistic data from Brazilian Portuguese (BP), and thus complement existing data, fill in gaps and later demarcate the different BP dialects, reconstruct the immigration history in Brazil, and research the evolution of BP. In Chapter 3 we investigate the mechanisms responsible for linguistic diversity in the Neotropical region (Mexico, Central and South America). We created a spatially explicit mechanistic model that incorporates altitude, water resources, precipitation and population group size as mechanisms capable of predicting the pre-Columbian linguistic diversity observed on the continent. In Chapter 4, we used a SIR (Susceptible, Infected, Removed) epidemiological model to assess the effectiveness of public policies of the state of Goiás in containing the spread of COVID-19 in its initial stage, between March and May 2020. In all chapters we successfully apply ecological theories and methods to data originated from humans, whether it's the language they speak or the virus that infects them. Therefore, we demonstrate how the methods and theories developed in biological disciplines can be applied to advance knowledge in the humanities, especially in linguistics and public administration. In this sense, we demonstrate the importance and effectiveness of multidisciplinary studies, especially for an object of study as complex as Homo sapiens.